An association of plasma cyclophilin A with severity of coronary artery disease - Parhad, Sachin; Bahulikar, Arun; Phalgune, Deepak; Tambolkar, Ajit; Patel, Divya (International Journal of Research in Medical Sciences, 2025)
Background: Plasma cyclophilin A (CyPA), an emerging biomarker of cardiovascular disease, is likely to play a crucial role in all stages of atherosclerosis. Very few studies have been conducted on the association of plasma CyPA with coronary artery disease (CAD) in India. The aim of the present study was to determine an association between plasma CyPA levels and CAD severity. Methods: The present cross-sectional observational study was conducted on 100 patients aged ≥18 years who presented with symptoms suggestive of CAD. The presence or absence of cardiovascular risk factors such as gender, hypertension, diabetes mellitus, dyslipidaemia, family H/O CAD, smoking, etc. were noted. Coronary angiography was performed on each patient. Quantitative estimation of plasma CypA levels and high-sensitivity C-reactive protein (hs-CRP) was done. Results: The mean serum CypA (66.6 Vs 44.9 ng/ml) and hs-CRP (29.8 Vs 21.4 mg/l) were significantly higher in patients with obstructive CAD as compared to non-obstructive CAD. There was a statistically significant positive correlation (r=0.251) between CypA levels and hs-CRP (p value=0.012). The mean low-density lipoprotein cholesterol (181 Vs 160.8 mg/dL) and mean triglycerides (179 Vs 168 mg/dl) were significantly higher in patients with obstructive CAD as compared to non-obstructive CAD. There was no statistically significant difference between the type of CAD and mean total cholesterol and high-density lipoprotein cholesterol. Conclusions: CypA levels were increased in obstructive CAD patients. High CypA serum levels could be a novel biomarker in CAD patients associated with severe CAD.